Implementation of the Naïve Bayes Method in Expert Systems for Diagnosing Achalasia - Ahmad Rozi (Universitas Medan Area, 2023)
The purpose of this research is to solve the problem of diagnosing achalasia, which the general public does not yet know about the treatment procedures. Achalasia is a condition in which the muscles of the esophagus fail to push food or drink into the stomach. This condition can cause symptoms such as difficulty swallowing, regurgitation of food into the esophagus, and weight loss. The sample data used by the authors for the process of diagnosing achalasia in this study were obtained from experts (experts) through literature study data collection techniques and field studies (interviews and observations). The expert system method implemented by the author to solve the problem of diagnosing achalasia in this study is the Naïve Bayes method. Naive Bayes is a method that can provide a solution by determining the probability values of a phenomenon. The results showed that the Naïve Bayes method was able to diagnose achalasia quickly and easily with accurate and reliable solutions. So that it can be used as a relevant alternative to help ordinary people get solutions to cure Achalasia.